Commercial suitability and characterization of newly developed Erucastrum canariense (Can) sterile cytoplasm based cytoplasmic male sterile (CMS) lines in Indian cauliflower - Manjunath, K. S.; Singh, Shrawan; Kalia, Pritam; Mangal, Manisha; Sharma, Brij Bihari; Singh, Naveen; Ray, Mrinmoy; Rao, Mahesh; Tomar, Bhoopal Singh (Scientific reports, 2024)
The study presents the first to characterize novel Erucastrum canarianse Webb and Berthel (or Can ) sterile cytoplasm-based CMS lines in Indian cauliflower ( Brassica oleracea var. botrytis L.) and investigating their commercial suitability. Eleven Can -based CMS lines were examined for 12 agro-morphological and yield traits,18 floral traits, four seed yield traits together with three each of the Ogura (source: wild Japanese Radish) and Tour (Source: Brassica tournefortii ) cytoplasms. All of the recorded floral and seed traits showed significant ( P > 0.05) differences between the CMS lines of each group. Agro-morphological and yield traits in CMS lines and their maintainers, however, were non-significantly different. All the Can- and Ogura- based CMS lines showed flowering and appropriate seed formation by natural cross-pollination. Only two Tour cytoplasm-based CMS lines, Tour (DC-41-5) and Tour (DC-67), produced the smallest malformed flowers and stigma. The highest seed yield per plant in CMS lines was in Ogu (DC-98-4) and the lowest in Tour (DC-67). P14 and P15, two polymorphic mtDNA markers, were discovered for the Can CMS system for early detection. Five primers (ITS5a-ITS4, atpF-atpH, P16, rbeL and trnL), along with their maintainers, were sequenced and aligned to detect nucleotide changes including as additions and or deletions at different positions. The newly introduced E . canariense sterile cytoplasm-based CMS system in cauliflower is the subject of the first comprehensive report, which emphasises their potential as a further stable and reliable genetic mechanism for hybrid breeding.